2012
DOI: 10.3390/s121013985
|View full text |Cite
|
Sign up to set email alerts
|

Physically-Based Reduced Order Modelling of a Uni-Axial Polysilicon MEMS Accelerometer

Abstract: In this paper, the mechanical response of a commercial off-the-shelf, uni-axial polysilicon MEMS accelerometer subject to drops is numerically investigated. To speed up the calculations, a simplified physically-based (beams and plate), two degrees of freedom model of the movable parts of the sensor is adopted. The capability and the accuracy of the model are assessed against three-dimensional finite element simulations, and against outcomes of experiments on instrumented samples. It is shown that the reduced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Specifically, the mechanical properties of polysilicon are characterized by a neural network, trained with the same data used in this work for upscaling its elastic properties [21][22][23][24]. Next step of the procedure is therefore the multiscale [25,26], fully data-driven analysis of the designed device and, to a larger extent, of the scattering measured in ever downsizing MEMS devices.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the mechanical properties of polysilicon are characterized by a neural network, trained with the same data used in this work for upscaling its elastic properties [21][22][23][24]. Next step of the procedure is therefore the multiscale [25,26], fully data-driven analysis of the designed device and, to a larger extent, of the scattering measured in ever downsizing MEMS devices.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, shocks still represent an important issue as for the reliability of inertial MEMS devices and failures linked to cracks spreading in high stressed regions of the MEMS can suddenly occur [ 26 ]. Focusing on the physical effects of shocks and drops on the MEMS accelerometer, it can be shown that the mechanical side of the problem is by far the most prominent one and the electrical side can be disregarded [ 27 ]. This is due to the fact the inertial and possible contact forces turn out to exceed by orders of magnitude the electrical ones, when more than is induced by the shock loading [ 24 ].…”
Section: Simulation Analysismentioning
confidence: 99%
“…Because of the re-entrant corners at the connection with the anchor and the substrate, is actually located in critical regions very close to the end of the cross-sections of the supporting beams [ 29 ]. What turned out from previous experiments is that standard accelerometers can sustain high-g acceleration levels without malfunctioning, since the stress field in critical regions results to be much below the characteristic tensile strength of silicon (typically higher than 1 GPa) [ 27 ]. As for traditional single torsional beam structures, the critical regions are near the symmetry line of the differential masses, where the moment of force is the maximum.…”
Section: Simulation Analysismentioning
confidence: 99%
“…The mentioned length scale separation is very important for computing the homogenized properties of the polysilicon films in multi-scale and, often, multi-physics analyses [13,14]. To avoid any surrogate or smoothing procedure of the available results, upscaling through a new Monte Carlo analysis thus looks necessary whenever the considered value does not match those already investigated.…”
Section: Introductionmentioning
confidence: 99%